The Armenian Language as a Remembrance and Manifestation of the Islamized Hamshenians’ Ethnic Identity - Sahakyan, Lusine (Armenian Folia Anglistika, 2007)
The article examines the language used by the present-day generation of the people of Islamized Hamshenians of Armenian origin as a memory and expression of their identity. As a result of the merging linguistic policy of the Ottoman Empire the vast majority of the generations of the Hamshen Armenians who were forced to convert to Muslim have become Turkish speaking in the course of time. Only the Hamshen Armenians in the state of Ardvin still preserve the dialect of Hamshen. The linguistic evidence presented in the article indicates that the dialect of the Hamshen Armenians in the state of Khopa is still viable today and that they keep speaking, telling stories and singing songs in that language. These written facts are valuable materials for Armenian philology and lexicology. These examples can help discover phonetic, grammatical and lexical similarities, differences between the Islamized Hamshen Armenians and Christian Hamshenians living on the northern coasts of the Black Sea.